Mengatasi Hambatan Komunikasi Horizontal PT.Masterindo Jaya Global Indonesia - Harmen, Hilma; Aprinawati; Nasution, Ahmad Zacky; Harahap, Gita Kusuma Dewi; Sidebang, Nitasari Lasma Uhur; Sitompul, Reginawati; Alvaro, Muhammad Rafli (Ikatan Da'i Indonesia, 2024)
This research aims to identify horizontal communication barriers faced by PT Masterindo Jaya Global Indonesia. Using a qualitative approach, descriptive data were obtained through literature study and observation of the research subjects, namely companies in Indonesia that experience horizontal communication problems. The results of qualitative data analysis show that communication barriers between units within the company can interfere with operational efficiency and effectiveness. Based on the findings, several solutions are proposed, such as choosing the right communication method, using easy-to-understand language, giving and asking for feedback in communication, increasing openness, maintaining harmonious inter-personal relationships, planning job placements correctly, and clarifying relationships within the organization. This research is expected to provide better insight into horizontal communication and provide guidance for managers and management system developers to improve communication effectiveness within the company.